An auditory perception and listening comprehension achievement test in English for grade I - Libas, Edelmira M. 1937- (1972)
The aim of the study is to construct a pool of items that may be used to determine auditory perception and comprehension of English critical sounds, vocabulary and structural items particularly those that are difficult for Tagalog learners of English at the beginning stage. It aims to determine how valid the items are in measuring auditory perception and listening comprehension skills, and how reliable the results are in measuring the achievement of grade I pupils in Biñan as far as auditory perception and listening comprehension skills are concerned.